2021
DOI: 10.3390/ijms22189996
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Phytomelatonin: Chemistry, Biosynthesis, Metabolism, Distribution and Bioactivity in Plants and Animals—An Overview

Abstract: Melatonin is a ubiquitous indolamine, largely investigated for its key role in the regulation of several physiological processes in both animals and plants. In the last century, it was reported that this molecule may be produced in high concentrations by several species belonging to the plant kingdom and stored in specialized tissues. In this review, the main information related to the chemistry of melatonin and its metabolism has been summarized. Furthermore, the biosynthetic pathway characteristics of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 345 publications
1
54
0
6
Order By: Relevance
“…The levels of melatonin are regulated by its rapid metabolism in the liver or directly at the site of its synthesis in peripheral organs [158]. In the classical hepatic metabolism, CYP450 enzymes (CYP1A1, CYP1A2, and CYP1B1) degrade circulating melatonin to 6-OH-melatonin [159,160].…”
Section: An Overview Of the Synthesis Metabolism And Function Of Mela...mentioning
confidence: 99%
“…The levels of melatonin are regulated by its rapid metabolism in the liver or directly at the site of its synthesis in peripheral organs [158]. In the classical hepatic metabolism, CYP450 enzymes (CYP1A1, CYP1A2, and CYP1B1) degrade circulating melatonin to 6-OH-melatonin [159,160].…”
Section: An Overview Of the Synthesis Metabolism And Function Of Mela...mentioning
confidence: 99%
“…Since melatonin synthesis, metabolism, signal transduction (Figure 1), target genes, and mechanisms of action have been extensively reviewed elsewhere, 86,96–99 it suffices to summarize here some salient features. Melatonin is synthesized in a multistep process from tryptophan 99 in the pineal gland and numerous “nonclassical,” extrapineal tissues in the human body such as skin and HFs (see below), 63,73 also in intact, wild‐type rodent (including mice) skin 58 .…”
Section: Introductionmentioning
confidence: 99%
“…82,83 Furthermore, the entire biochemical machinery necessary for transforming L-tryptophan into melatonin is expressed in all main tissue compartments of human skin, by epidermal and HF keratinocytes and melanocytes, dermal fibroblasts, and even mast cells. 60,[83][84][85] Since melatonin synthesis, metabolism, signal transduction (Figure 1), target genes, and mechanisms of action have been extensively reviewed elsewhere, 86,[96][97][98][99] it suffices to summarize here some salient features. Melatonin is synthesized in a multistep process from tryptophan 99 in the pineal gland and numerous "nonclassical," extrapineal tissues in the human body such as skin and HFs (see below), 63,73 also in intact, wild-type rodent (including mice) skin.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytrytamine [MLT]) is a tryptophan-derived indolamine and it acts as a wellknown protective agent in both animals and plants. [1][2][3][4][5] One of the important functions of MLT is that it can protect cells from various oxidants, including reactive oxygen species (ROS) and reactive nitrogen species (RNS). 6,7 Recently, mounting evidence has shown that MLT not only acts as an antioxidant but also triggers substantial changes in gene expression involved in diverse physiological processes, reflecting a pleiotropic role of MLT in organisms.…”
Section: Introductionmentioning
confidence: 99%